Biology, ecology and management of the Keurboom moth, Leto venus Cramer and the leafhopper Molopopterus sp. Jacobi in cultivated Honeybush (Cyclopia spp.) - Mushore, Tapiwa Gift (Rhodes University, Faculty of Science, Department of Zoology and Entomology)
Honeybush, Cyclopia spp. Vent (Fabaceae), farmers have raised pest concerns following commercial cultivation. The Keurboom moth Leto venus Cramer (Lepidoptera: Hepialidae) and the leafhopper Molopopterus sp. Jacobi (Hemiptera: Cicadellidae), are two of the major pests identified in cultivated Honeybush. Laboratory and field studies were conducted to gain an understanding of the biology of these two pests to inform future pest management solutions. Additionally, entomopathogenic fungi were isolated from Honeybush farms and screened for virulence against Molopopterus sp. as a possible management strategy. This study showed that the L. venus infestation on Honeybush was a product of four fixed effects; stem diameter, species of Cyclopia, Farm location and age of the plants. Cyclopia subternata, had the highest likelihood of infestation. Increase in age of the plants resulted in an increase in the stem diameter and therefore a higher probability of infestation. Stem diameter was also shown to be a significant predictor of infestation likelihood. Infestation severity, determined by the number of larvae per plant, was shown to be influenced by three fixed effects; stem diameter, plant species and Farm location. The results also showed that L. venus prefers to initiate penetration at, or just aboveground level. Laboratory studies showed that the leafhopper Molopopterus sp. undergoes five nymphal instars with an average egg incubation time of 20 days, development time from 1st instar to adult of 26 days and average generation time of 47 days. Laboratory experiments revealed variations in host preference by the leafhopper over a period of 15 days. Cyclopia longifolia was identified to be the most preferred species for feeding compared to the two other commonly cultivated species, C. subternata and C. maculata. The results were consistent with those obtained from the field survey which showed that leafhopper density was influenced by four fixed effects; plant species, age of the plant, Farm location and harvesting practices. There were significant differences in leafhopper density in different species with C. longifolia having the highest number of leafhoppers per plant. There were differences in leafhopper density in different farms as 57% of the sampled farms had leafhopper infestations, of these farms, Lodestone and Kurland had the highest leafhopper densities. Harvested plants were shown to have significantly higher leafhopper density than non-harvested plants. Age was also shown to influence leafhopper density, which reduced with an increase in the age of the plants. A total of 20 fungal isolates were recovered from 98 soil samples of which 70% were from Honeybush fields and 30% were from surrounding refugia. Fusarium oxysporum isolates comprised 20% of the recovered isolates, with Metarhizium anisopliae isolates making up the remainder. Laboratory bioassays against adults and nymphs of the leafhopper, Molopopterus sp., showed that F. oxysporum isolates induced 10 "“ 45% mortality and M. anisopliae isolates induce 30 "“ 80% mortality. Metarhizium anisopliae isolates J S1, KF S3, KF S11, KF S13, LS1 and LS2 were the most virulent and induced over 60% mortality in both Molopopterus sp. nymphs and adults. The results of this study showed pest preference towards different Cyclopia species. As such, they should be managed differently. Furthermore, L. venus was observed to occur in low densities, hence, it cannot be considered a major pest. However, Molopopterus sp. recorded high population densities making it a major pest in Honeybush production. Positive results indicated that some of the isolated fungal isolates have potential for control, an avenue worth investigating further.
Keywords: Legumes; Legumes -- Diseases and pests; Hepialidae; Leafhoppers; Pests -- Biological control; Entomopathogenic fungi; Leafhoppers -- Biological control; Hepialidae -- Biological control; Keurboom moth (Leto venus Cramer); Molopopterus sp. Jacobi; Honeybush (Cyclopia spp.)